매체 유형에 따른 헬스케어 커뮤니케이션 캠페인 효과 분석 - 인쇄물과 영상 미디어 중심으로 - 배순한; 이지수; 최재영; Bae, Soonhan; Lee, Jisoo; Choi, Jaeyoung ((사)디지털산업정보학회 논문지, 16(4), 2020)
With increasing social interest in health and health promotion, the government and many organizations are conducting various health campaigns for the public. The public health campaign is aimed at protecting the people from the dangers of disease and contributing to a healthy life and also help establishing a healthy attitude and changing behavior as well. In addition, many researches have been carried out in order to enhance the advertising effect of campaigns aimed at forming preventive attitudes and to verify it by applying many theories. However, as a result, there is a significant lack of research regarding analysis of differences in the effectiveness of the campaign by media. This study is to analyze the effect of health campaign by the type of media which published health campaign advertisements that can affect prevention attitude. To meet the purpose of this study, The 15 print media were to examine the impact of media characteristics and types on participation in campaigns for health campaigns. Through this, we will present the role of the media as an efficient channel to encourage the formation and participation of the health attitude of campaign advertisements, and present significant implications in the selection of optimal media and the execution of campaign budgets.